Oral Rehydration Therapy: WHO at 40, ORT at 30 - Jonathan LaPook; Richard N. Fedorak (Canadian Journal of Gastroenterology)
Oral rehydration therapy may prove to be mankind's most significant therapeutic advance this century. Diarrheal disease remains the number one killer of children in the world and is a major cause of illness within Canada and other developed countries. Since its discovery 30 years ago, oral rehydration therapy, comprising glucose, salt and water, has been a simple and low cost treatment for people with life threatening diarrheal disease. Recent developments in solutions for oral rehydration therapy have led to the recognition chat the existing World Health Organization glucose based oral replacement salt could be improved. ln commercially available rehydration solutions, the sodium concentration has been lowered to reduce hypernatremia in noncholera induced diarrhea. Citrate has replaced bicarbonate as the base in oral replacement solutions to pro long shelf life. Organic substrates to replace glucose and enhance intestinal fluid and electrolyte absorption without osmotic penalty are being examined. However, their acceptance and proper utilization in developing countries remains to be determined.